From Roots to Routes: Diasporic Sensibility in And the Mountains Echoed - Dr Rizwan Akhtar, Munazza Majeed* & (Journal of Research in Humanities, 2020)
In this article I argue that the characters in Khaled Hosseini’s And the Mountains Echoed reflect a unique diasporic sensibility: concurrently divided between desires for reclaiming Afghan roots and of exploring alternative routes to reach out their lost roots. I discuss the novel And the Mountains Echoed from the theoretical lens of discourse on diaspora, mainly by the diaspora theorists Stuart Hall and Edward Said. The characters in Hosseini’s novel return to their ancestral homeland, both imaginatively and literally. For this two-fold journey they take manifold routes in order to restore and renew their ties with their Afghan roots. Thus the expatriates exhibit the perennial predicament of a diasporic subject straddling between the vulnerable guide-posts of home and exile. Their homecoming only makes them realize the impossibility to return. When the characters in the novel realize impossibility of return, the certainties of roots are replaced with the transnational contingencies of routes.